Early maladaptive schemas as mediators between childhood maltreatment and later psychological distress among Chinese college students. (January 2018) - Gong, Jingbo; Chan, Raymond C.K.
Abstract: The aim of the current study was to examine whether early maladaptive schemas (EMSs) mediate the association between different kinds of childhood maltreatment and later psychopathology and the effect of different kinds of childhood maltreatment on psychological distress in later life. A total of 1102 college students from two local universities participated in the study; their average age was 20.46 ± 1.13 years. The participants completed the Childhood Trauma Questionnaire (CTQ), the Early Maladaptive Schemas Scale (EMSs), the Zung Self-Rating Depression Scale (SDS), and the Zung Self-Rating Anxiety Scale (SAS). Later psychological distress had a significant positive correlation with childhood EMSs, and almost all of the variables measuring childhood maltreatment had a significant positive correlation with EMSs. Structural equation modeling and mediation analyses were conducted based on Bootstrap estimations; the mediation analyses demonstrated the utility of EMSs as the mechanism through which childhood maltreatment has an indirect effect on later psychological distress. Moreover, the study found that emotional abuse had the strongest overall effect of all five types of child maltreatment on later psychological distress, followed in order of magnitude by emotional neglect, physical neglect, sexual abuse, and physical abuse. Highlights: Examining the association between CM and psychology in Chinese Han population. EMSs mediated indirectly between CM and subsequent psychological distress. Emotional abuse had the strongest effect on subsequent psychological distress.